Reinterpretasi Ayat-Ayat Silaturahmi Di Era Digital: Upaya Membangun Interaksi Sosial Perspektif Al-Qur’an - Arif Dika Prasetya; Syifa Maulani (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Digital transformation has reshaped patterns of social interaction, including the practice of silaturahmi. Previously associated with face-to-face meetings that foster emotional closeness, these relationships are now increasingly conducted through virtual media. This situation creates a social paradox: technology expands connectivity, yet it may reduce the depth of relationships and the spiritual value of human interaction. This study aims to reinterpret Qur’anic verses on silaturahmi and to formulate Qur’anic guidelines for building social interaction in the digital era. The method used is a qualitative approach through library research with a thematic (maudhu’i) tafsir analysis. The findings indicate that silaturahmi has two main dimensions: yuushola, which emphasizes the spiritual relationship with Allah, and al-arham, which emphasizes social relationships among people. Both dimensions form the ethical foundation of social interaction. In the digital context, these values can be implemented by positioning technology as a means (wasilah) rather than an end (ghayah), preventing relational damage and digital isolation, and balancing virtual interactions with face-to-face encounters. Thus, digital technology can be utilized to strengthen silaturahmi in accordance with Qur’anic values in a sustainable manner